EVALUASI KEBERLANJUTAN PROGRAM BANTUAN LANGSUNG TUNAI DALAM UPAYA PENANGGULANGAN KEMISKINAN, TINJAUAN DARI ASPEK KEBIJAKAN DAN ANGGARAN (Studi Kasus Desa Padang Binjai Kecamatan Tetap Kabupaten Kaur) - Mardianto, Mardianto; Aprianty, Henny; Dani, Rahiman (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2025)
This study aims to analyze the evaluation of the implementation of BLT-DD in Padang Binjai Village, Tetap District, Kaur Regency, reviewed from the policy and budget aspects. To analyze the factors that influence the implementation of the BLT-DD Program in Padang Binjai Village, Tetap District, Kaur Regency. To answer these problems, researchers use qualitative research methods. The results of the study indicate that in the context evaluation process, the Village Fund Direct Cash Assistance (BLT-DD) service has been completely good. Based on the results of the study Evaluation of the Sustainability of the Direct Cash Assistance Program in Poverty Alleviation Efforts, a Review of Policy and Budget Aspects, an evaluation was carried out using the CIPP model evaluation which includes context evaluation, Inpt evaluation, Process evaluation, product evaluation: 1. Context Evaluation: BLT-DD services have met the criteria even though some who received this assistance were assisted by their relatives who work at the village office. 2. Input Evaluation: all residents in Padang Binjai Village who received BLT-DD have used the assistance well according to their needs. 3. Process Evaluation: Not all recipients of Village Fund Direct Cash Assistance (BLT-DD) are from lower-income families, but they take advantage of their relatives who work at the Village Office to gain access to assistance. 4. Product Evaluation: In the future, village officials will be more transparent regarding data on BLT-DD recipients and who is eligible to receive it to avoid social jealousy among those who do not receive it.